Penerapan Arsitektur Biophilic pada Bangunan Pet Care Center di Pekanbaru - Rasid, Fikra; Samra, Boby; Nurdin, Apriliana Hidayati (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2025)
Public awareness of pet welfare has experienced significant development in recent decades, along with the increasing number of people adopting and keeping animals. With this increase, awareness of pet hygiene is increasing. This situation gives rise to an urgent need for professional and comprehensive care services. The goal of this plan is to design a building design that focuses on the welfare of pets and their owners. This research applies qualitative-descriptive methods. This Pet Care Center is a facility that has health, care and day care facilities for pets. Apart from that, it also functions as an information center, recreation area, and also as a place for interaction between fellow animal lovers in Pekanbaru City. The concept of planning this Pet Care Center is to use "Biophilic Architecture", a concept that prioritizes animal integration and welfare in the space. It is hoped that the design of this Pet Care Center can provide education to owners about how to care for animals, understand animal behavior and also about animal health problems.